The Importance of Empowering RTs in Optimizing Population Data Services in Karangpoh Village, Tandes District, Surabaya: Pentingnya Pemberdayaan RT Dalam Optimalisasi Pelayanan Data Kependudukan Di Kelurahan Karangpoh, Kecamatan Tandes, Surabaya - Evi Rohmatul Laili (Yayasan Ahmar Cendekia Indonesia, 2023)
Population administration is an important document, generally speaking, in fact many citizens ignore population administration, resulting in the de facto not being in line with the de jure. This can affect development and equality and can influence policy formulation, especially in the health sector. Based on these problems, the Surabaya City Population and Civil Registration Department created the KALIMASADA (Population Administration Aware Community Environmental Area). To realize the program objectives, assistance was provided to increase the knowledge and ability of the KALIMASADA RT in entering population documents so that the RT becomes empowered and can create an environmental area, a community that is aware of population administration. The results obtained are that the RTs that run KALIMASADA are implementing how to use KNG, and there is an improvement in the way RT heads provide solutions related to the problems faced by residents regarding the management of their population administration documents.